Automatic Salt Fish Drying Machine Development Process Using MEDP - RUBANI, SITI NUR KAMARIAH; Zakaria, Normah; Hamzah, Norhasyimah; Ariffin, Arihasnida (Research and Innovation in Technical and Vocational Education and Training, 2023)
Drying is one method of preserved using simple techniques, such as sun-drying. However, weather conditions are usually unpredictable, and this drying process will be hindered when the rainy season comes. As a result, dried fish will take longer to dry and will be produced with less efficiency. The development of complex machinery has made the drying process less challenging. Therefore, the aim of this study is to design, develop, and test an automatic salted fish drying machine to assist in the solution of the dried fish problem. The Model Engineering Development Product (MEDP) utilized in the study contains five phases: identification of the problem, making possible solutions, prototype development design, modelling the best solution, refinement, and retesting the model. The sensor alerts the Arduino microcontroller when raindrops are found. The Arduino commands the motor to move the roof to keep dry fish from becoming wet. Overall, it was found that the automatic salted fish drying machine worked well and achieved the study’s objective. However, the product needs to be improved to allow the fish to continue drying during rain.